2009
DOI: 10.1103/physrevlett.103.208301
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity of Arrested Short-Ranged Attractive Colloids: Homogeneous and Heterogeneous Glasses

Abstract: We evaluate the elasticity of arrested short-ranged attractive colloids by combining an analytically solvable elastic model with a hierarchical arrest scheme into a new approach, which allows to discriminate the microscopic (primary particle-level) from the mesoscopic (cluster-level) contribution to the macroscopic shear modulus. The results quantitatively predict experimental data in a wide range of volume fractions and indicate in which cases the relevant contribution is due to mesoscopic structures. On this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
96
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 39 publications
11
96
0
Order By: Relevance
“…The final arrested plateau value of the elastic modulus, G p , increases dramatically with increasing quench depth by nearly an order of magnitude. 74 For larger values of L c (i.e. 42 This is captured in Fig.…”
Section: Quench-dependence Of the Arrested Statementioning
confidence: 83%
“…The final arrested plateau value of the elastic modulus, G p , increases dramatically with increasing quench depth by nearly an order of magnitude. 74 For larger values of L c (i.e. 42 This is captured in Fig.…”
Section: Quench-dependence Of the Arrested Statementioning
confidence: 83%
“…Various approaches have been proposed to explain a) Author to whom correspondence should be addressed; electronic mail: jan.vermant@mat.ethz.ch these properties, with most theories focusing on the structure at rest. For strong gels, fractal scalings [7,8] and poroelastic models [9] have been proposed linking the elasticity of the gel network to the rigidity of intra-or interfloc links [7,10]. In weaker gels with more of a bicontinuous, disordered morphology, it has been suggested that the elasticity is determined by the localization of particles in the gel, which slows down the Brownian relaxation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, altering the strength and range of the attractions at the origin of colloidal gelation enables tailoring the properties of colloidal dispersions to wider-ranging and challenging applications, from foodstuff and cosmetics to pharmaceutical and chemical products. In the recent years, advances in modeling and simulation [Zaccone et al (2009);Zaccarelli (2007); Del Gado and Kob (2007);a) Author to whom correspondence should be addressed; electronic mail: dvlasso@iesl.forth.gr V C 2014 by The Society of Rheology, Inc. J. Rheol. 58(5), 1441-1462September/October (2014 0148-6055/2014/58(5)/1441/22/$30.00 Puertas et al (2004); Cates et al (2004); Ramakrishan et al (2002); Mao et al (1995)] and the emergence of (hard) colloid-polymer mixtures as an ideal model system for exploring the whole range of colloidal behaviors from dilute gels to dense glasses [Pham et al (2002); Poon (2002)] gave a new boost to the field and triggered new efforts (experimental and modeling/simulations) toward the fundamental understanding of phenomena related to colloidal gelation.…”
Section: Introductionmentioning
confidence: 99%